2013
DOI: 10.1111/1462-2920.12199
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater bacterial lifestyles inferred from comparative genomics

Abstract: While micro-organisms actively mediate and participate in freshwater ecosystem services, we know little about freshwater microbial genetic diversity. Genome sequences are available for many bacteria from the human microbiome and the ocean (over 800 and 200, respectively), but only two freshwater genomes are currently available: the streamlined genomes of Polynucleobacter necessarius ssp. asymbioticus and the Actinobacterium AcI-B1. Here, we sequenced and analysed draft genomes of eight phylogentically diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…The oligotype assignments to lifestyle strategies generally supported existing knowledge about the ecology of these lineages. Freshwater Actinobacteria lineage acI, Alphaproteobacteria lineage LD12, and some members of the genus Polynucleobacter are considered ubiquitous, abundant members of freshwater lakes (Newton et al 2011) with passive oligotrophic lifestyles (Hahn et al 2012, Ghylin et al 2014, Livermore et al 2014. This assertion supports generally the spatial/temporal patterns we observed in Lake Michigan surface waters, where 15 oligotypes from these groups were classified as having oligotroph-like distribution patterns, including both abundant (≥0.1% maximum) and rare members.…”
Section: Trophic Strategy and Rarity In Aquatic Environments: Case Stsupporting
confidence: 83%
See 3 more Smart Citations
“…The oligotype assignments to lifestyle strategies generally supported existing knowledge about the ecology of these lineages. Freshwater Actinobacteria lineage acI, Alphaproteobacteria lineage LD12, and some members of the genus Polynucleobacter are considered ubiquitous, abundant members of freshwater lakes (Newton et al 2011) with passive oligotrophic lifestyles (Hahn et al 2012, Ghylin et al 2014, Livermore et al 2014. This assertion supports generally the spatial/temporal patterns we observed in Lake Michigan surface waters, where 15 oligotypes from these groups were classified as having oligotroph-like distribution patterns, including both abundant (≥0.1% maximum) and rare members.…”
Section: Trophic Strategy and Rarity In Aquatic Environments: Case Stsupporting
confidence: 83%
“…Marine copiotrophs also had relatively more exoenzymes, which were hypothesized to be related to a predominately particle-associated lifestyle. Similarly, it has been suggested that copiotrophs are more likely to be motile (Livermore et al 2014, Lever et al 2015, have larger investments in signal transduction mechanisms, and have the genetic capacity to use a wider array of carbon substrates (Livermore et al 2014). Finally, there was some evidence that oligotrophs have more secondary metabolite biosynthetic pathways (Lauro et al 2009).…”
Section: Heterotrophic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, genome size and the number of metabolic pathways may distinguish generalists and specialist organisms 30 . Furthermore, gene transition rates may provide evidence into evolutionary strategies and high rates may be a signature of evolutionary diversification.…”
mentioning
confidence: 99%